Multicultural-Based Islamic Education Curriculum Design for Strengthening Religious and Tolerant Character - Rifai, Mohammad Rohman; Ariana, Widya; Rohman, Muhammad Ainur; Zahiduzzaka, Muhammad Faza; Rivaldi , Muhammad Fauzan (Ahlussunnah: Journal of Islamic Education, 2026)
Moral problems among students, reflected in declining digital ethics, low empathy, verbal bullying, symbolic violence, and religious exclusivism, indicate that Islamic Religious Education learning remains overly focused on normative knowledge transfer. This study aims to formulate a multicultural-based Islamic education curriculum design for strengthening students’ religious and tolerant character. The study employed a qualitative method using a content analysis approach. Data were obtained from scholarly journal articles, curriculum and multicultural education books, character education literature, and religious moderation documents. The data were analyzed through literature reduction, thematic categorization, interpretation, and conceptual synthesis. The findings propose the DAK-PM model (Multicultural Islamic Education Curriculum Algorithmic Design), which consists of six stages: diagnosing moral problems, mapping learning outcomes and learning objectives, integrating multicultural values, designing dialogic-collaborative pedagogy, conducting authentic character assessment, and curriculum reflection and revision. The model integrates Tyler’s curriculum rationale, Taba’s inductive curriculum model, Banks’ multicultural education dimensions, Gay’s culturally responsive pedagogy, and Lickona’s character education framework. The study implies that Islamic education curricula should be transformed into a learning ecosystem that balances ritual religiosity, social morality, diversity literacy, digital ethics, and peaceful living skills in multicultural societies.